Experimental Investigation of a Temperature Change inside Pneumatic Cylinder Chambers - Hassan, Jafar M.; Ghanim, Dheya; Hamandy, Noor B. (Al-Nahrain Journal for Engineering Sciences, 2017)
The investigation of the existence of a tempera-ture change with pressure inside the pneumatic cylinder chambers during the charging and dis-charging strokes in the pneumatic cylinder is ex-perimentally demonstrated. Three different varia-bles (pressure, piston displacement and tempera-ture) were measured in this work while operating with a servo pneumatic system and a discussion of the relationship between these variables was pre-sented. The cylinder used has a piston diameter of (0.05m), piston rod diameter (0.02m) and a stroke length of (0.2m). The results show a temperature rise of 23 K above atmospheric temperature at chamber (1) while air compressing and a tempera-ture drop of 17 K below atmospheric temperature at chamber (2) while air expansion and measures other temperature changes also.